Analisis manajemen risiko reputasi pada bank syariah di era media sosial: Pendekatan sentimen nasabah digital - Anita, Dinda Rosmaya (Maliki Interdisciplinary Journal, 2026)
The proliferation of social media platforms such as Twitter and Instagram has increased the complexity of reputational risk in Islamic banks, as customer opinions can rapidly influence public perception. This study aims to analyze reputational risk management using a digital customer sentiment analysis approach. The results show that social media acts as both a source of risk and a strategic tool for building reputation. Sentiment analysis is effective for early detection of customer perceptions and potential crises. Required strategies include responsive and transparent digital communications and the use of real-time social media monitoring. Furthermore, the integration of data-driven analytical technology is a crucial factor in improving the accuracy of sentiment mapping and enabling faster and more accurate decision-making. Islamic banks need to develop adaptive risk management systems that combine preventive and responsive approaches to the dynamics of public opinion in the digital space. These findings emphasize that reputation management should no longer be reactive but rather proactive and sustainable. Therefore, optimizing sentiment analysis serves not only as a risk detection tool but also as a strategic instrument to strengthen customer trust and maintain the stability of an institution's reputation in the digital era.